2014
DOI: 10.1371/journal.pone.0112415
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD112 Expression in Methylcholanthrene-Induced Tumors in CD155-Deficient Mice

Abstract: Tumor recognition by immune effector cells is mediated by antigen receptors and a variety of adhesion and costimulatory molecules. The evidence accumulated since the identification of CD155 and CD112 as ligands for DNAM-1 in humans and mice has suggested that the interactions between DNAM-1 and its ligands play an important role in T cell– and natural killer (NK) cell–mediated recognition and lysis of tumor cells. We have previously demonstrated that methylcholanthrane (MCA) accelerates tumor development in DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Recent studies looked at the role of CD155 in MCA-induced tumors and were not able to show any difference in tumor growth in the absence of CD155. 53 Interestingly, they found that CD112 expression was upregulated in CD155-deficient mice suggesting that the two ligands can redundantly regulate T-cell responses to maintain suppression of the immune response. 53 This could be due to preferential interaction of TIGIT with CD112.…”
Section: Role Of Cd112 and Cd155 Ligands In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies looked at the role of CD155 in MCA-induced tumors and were not able to show any difference in tumor growth in the absence of CD155. 53 Interestingly, they found that CD112 expression was upregulated in CD155-deficient mice suggesting that the two ligands can redundantly regulate T-cell responses to maintain suppression of the immune response. 53 This could be due to preferential interaction of TIGIT with CD112.…”
Section: Role Of Cd112 and Cd155 Ligands In Cancermentioning
confidence: 99%
“…53 Interestingly, they found that CD112 expression was upregulated in CD155-deficient mice suggesting that the two ligands can redundantly regulate T-cell responses to maintain suppression of the immune response. 53 This could be due to preferential interaction of TIGIT with CD112. However, the TIGIT-CD112 interaction is not very strong.…”
Section: Role Of Cd112 and Cd155 Ligands In Cancermentioning
confidence: 99%
“…Similar to findings regarding NKG2D ligands, over‐expression of DNAM‐1Ls is considered a critical danger signal that alerts cytotoxic cells to combat tumour cells. Therefore, CD155 appears to play dual roles in eliminating and promoting tumours …”
Section: Dnam‐1 In the Control Of Cancermentioning
confidence: 99%
“…Therefore, CD155 appears to play dual roles in eliminating and promoting tumours. 74 The induction of DNAM-1L expression on tumour cells is a promising therapeutic strategy for cancer. The DNAM-1 receptor system has already been used as a target for anti-cancer therapies.…”
Section: Dnam-1 In the Control Of Cancermentioning
confidence: 99%
“…Distinctive examples are DNAM-1, TIGIT, and CD96, all critical regulators of NK cell function which share CD155 and CD112 ligands (members of nectin and nectin-like protein families) [10]. CD155 is a dominant ligand over CD112 for DNAM-1 and TIGIT [11]. CD155 (Necl5, PVR, Tage4) is an immunoglobulin-like receptor found on certain tumors [10,12,13].…”
Section: Analysis Of Cytokine Productionmentioning
confidence: 99%